2021
DOI: 10.3390/en14217430
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impacts of Economic, Social, and Environmental Factors on the Relationship between Urbanization and CO2 Emissions

Abstract: This study examines the relationship between urbanization, economic growth, industrial transformation, technological change, public services, demographical change, urban and natural environmental changes, and carbon emissions using a dataset of 182 prefecture-level cities in China between 2001 and 2010. Specifically, this paper differs from previous studies in two aspects. First, the extant literature has focused on how economic processes accompanying rapid urbanization affect carbon emissions in urban areas b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…The urbanisation process will inevitably have an impact on increasing the use of energy, resulting in the emission of large amounts of greenhouse gases such as CO 2 (Haouraji et al, 2021;Mata et al, 2021;Pang et al, 2021). Ding et al (2021) analysed the impact of 182 prefecture-level cities in China on carbon emissions during rapid urbanisation. They found that urban construction increases the growth of carbon emissions (Ding et al, 2021).…”
Section: Impact Of Urbanisation On Carbon Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The urbanisation process will inevitably have an impact on increasing the use of energy, resulting in the emission of large amounts of greenhouse gases such as CO 2 (Haouraji et al, 2021;Mata et al, 2021;Pang et al, 2021). Ding et al (2021) analysed the impact of 182 prefecture-level cities in China on carbon emissions during rapid urbanisation. They found that urban construction increases the growth of carbon emissions (Ding et al, 2021).…”
Section: Impact Of Urbanisation On Carbon Emissionsmentioning
confidence: 99%
“…Ding et al (2021) analysed the impact of 182 prefecture-level cities in China on carbon emissions during rapid urbanisation. They found that urban construction increases the growth of carbon emissions (Ding et al, 2021). Liu et al (2022) found that under China's new urbanisation scenario, the population-land-economic urbanisation (PLEU) coupling coordination degree has an inverted U-shaped effect on carbon emissions and gradually tends to decrease as the PLEU coupling coordination degree is high to a certain degree (Liu et al, 2022).…”
Section: Impact Of Urbanisation On Carbon Emissionsmentioning
confidence: 99%
“…Urbanization processes have a significant impact on carbon dioxide emissions in urban areas. Numerous studies have focused on the relationship between economic processes and carbon dioxide emissions in urban areas [25]; however, these studies have shown that as cities become more urbanized, there is a corresponding increase in carbon dioxide emissions [26]. However, in recent years, there has been growing concern about the impact of communication technology infrastructure on CO 2 emissions [27].…”
Section: Introductionmentioning
confidence: 99%
“…According to a crude development pattern, China achieves economic growth by consuming Land 2022, 11, 1079 2 of 16 large amounts of energy, resulting in a rapid increase in carbon emissions [3], and the most important driving factor exacerbating this situation is rapid urbanization [4]. The urbanization rate of China has increased dramatically over the last four decades, from 17.9% in 1978 to 60.6% in 2019 [5], and the urban population of the country is expected to surpass 75% of the overall population by 2050 [6]. Urbanization is accompanied by industrial economic growth, increasing energy consumption, lifestyle changes, and changes in land use types due to economic and social progress, all of which have a significant influence on carbon emissions [7].…”
Section: Introductionmentioning
confidence: 99%